Zmanjšanje tlačnih izgub v vročevodnih cevnih mrežah - Krope, Andrej (Strojniški vestnik, 2000)
In the paper the impact of cationic surfactant additives on reducing the turbulence in the hot-water pipelines of district heating system is presented. With small ammonts of cationic surfactants in district-heating water the friction losses in pipeline can be reduced significantly. Because of this effect the pressure drops are decreased what leads to reductions in pump energy, pumping costs, costs of gas for heating the supply water, heat losses and to an increase in the heat capacity. New district-heating networks can be designed with smaller pipe diameters and so investment costs can be reduced significantly by applying friction-reducing additives.
Keywords: pretok fluida; izgube tlačne; dodatki; sistemi toplovodni; tlačne izgube; cevovodi; površinsko aktivne snovi